2020
DOI: 10.1038/s41598-020-72856-0
|View full text |Cite
|
Sign up to set email alerts
|

Infralimbic cortex controls fear memory generalization and susceptibility to extinction during consolidation

Abstract: Lesioning or inactivating the infralimbic (IL) subregion of the medial prefrontal cortex before acquisition produces more generalized and extinction-resistant fear memories. However, whether and how it modulates memory specificity and extinction susceptibility while consolidation takes place is still unknown. The present study aims to investigate these questions using muscimol-induced temporary inactivation and anisomycin-induced protein synthesis inhibition in the rat IL following contextual fear conditioning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 58 publications
1
17
0
Order By: Relevance
“…Inactivation of IL with muscimol and lidocaine before extinction learning was sufficient to impair the consolidation of extinction learning [55,56]. Finally, treatment with the protein synthesis inhibitor anisomycin before extinction training affected the reconsolidation of extinction training and susceptibility to extinction training [56,57].…”
Section: Role Of the Il In Fear Memory Extinctionmentioning
confidence: 99%
“…Inactivation of IL with muscimol and lidocaine before extinction learning was sufficient to impair the consolidation of extinction learning [55,56]. Finally, treatment with the protein synthesis inhibitor anisomycin before extinction training affected the reconsolidation of extinction training and susceptibility to extinction training [56,57].…”
Section: Role Of the Il In Fear Memory Extinctionmentioning
confidence: 99%
“…Two neuronal subpopulations encoding either fear or safety after extinction were identified, both projecting to the mPFC but part of distinct neuronal circuits: BLA fear neurons received input mainly from the ventral HPC and extinction neurons from the mPFC. Subsequent studies confirmed that fear and extinction neurons project to the PL or the IL, respectively [71][72][73].…”
Section: Mpfc Functional Inputsmentioning
confidence: 83%
“…This theory would explain how new schemas can be integrated faster into an existing framework that was previously learned [88]. It is supported by studies highlighting the role of the HPC at late times post-encoding [49,63], of the mPFC at early times [9,10,[53][54][55][56]71], as well as by reports of distributed engram cells throughout the brain [31,39,[89][90][91][92][93].…”
Section: The Multiple Trace Theory (Mtt)mentioning
confidence: 88%
See 1 more Smart Citation
“…The input driving the NR-CA1 pathway is most likely from the mPFC, encompassing both the prelimbic (PL) and infralimbic (IL) regions. While PL is needed for fear acquisition and retrieval, IL is necessary for the opposing task of fear suppression and preventing overgeneralization [56][57][58][59] . The likely opposing influences of IL and PL on NR during CFMR illustrates the importance of understanding NR output pathways.…”
Section: Discussionmentioning
confidence: 99%